A Rare Case of Concrescence of Mandibular Third Molar and Supernumerary Fourth Molar - Jiao Wang; Errui Wang; Xin Yang; Lu Yuan; Zhige Li; Jie Zhang; Baoping Zhang (Hindawi Limited, 2022)
Concrescence reveals a rare developmental anomaly in which two fully formed teeth are joined along the root surfaces by cementum, and generally occurs in maxillary molars, especially in a third molar and a supernumerary tooth. Very few cases have been reported about the concrescence of a third molar and a supernumerary fourth molar. Based on our available knowledge, this case report described a rare presentation in which concrescence is observed between a third molar and a supernumerary fourth molar in the mandible by diagnosing with cone-beam CT and histological examination.